Types andDensity of Microplastic in The Coastal Area of Pariaman Regency, Sumatera Barat Province - Annesa Fista Savitri; Adriman Adriman; Eni Sumiarsih (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRAC  Pariaman Regency coastal area is affected by current and tide from Indian Ocean that contribute the presence of microplastic in that area. To understand the microplastic types and density, a research has been conducted in May-July 2019. There were 3 sampling sites (Pantai Mangguang, Pantai Ampalu and Pantai Gandoriah) and there were 3 plots (50x50 cm) placed in each site. Sediment inside the plot was scrapped 5 cm depth. The sediment was then sieved (5 and 1 mm mesh size), dried and soaked in 35% NaCl. The floating microplastics were then collected and identified using a dissecting microscope. Results shown that there were 4 types of microplastic present, they were film, fragmen, fiber and foam. The most common microplastic found was film (1,360item/m3). The density of microplastic found in the sampling site ranges from 400 - 1,840 item/m3. In the intertidal zone, the highest density of microplastic was found in the highest tidal level (2000 item/m3). Keywords: Plastic Pollution, Intertidal Zone, Sediment, Film.